Dynamics of volume of competition practice and facilities of training of jumpers in length and triple in the process of long-term preparation - Sovenko S.P; Kolot A.V (Kharkov National Pedagogical University, 2012)
Analysed and systematized information in relation to the volume of competition practice and facilities of different primary orientation of jumpers in length and triple in the process of long-term preparation. The expert questioning is conducted 16 trainers. The documents of planning of training process are analysed, the analysis of diaries of sportsmen is carried out (n=22). The volume of competition practice of sportsmen and facilities of training of different primary orientation is certain. The results of analysis in relation to the construction of training process are reflected by the leading trainers of Ukraine on track-and-field. An approach classification of facilities of training taking into account the specific of training process of sportsmen is presented. It is set that the volume of facilities of general preparation is most on the initial stages of long-term perfection, then stabilized on the stages specialized base and preparations to higher achievements and a few diminishes on maximal implementation of individual possibilities and maintainance of higher sporting trade phases. It is related to diminishing of duration of the general preparatory stages of annual preparation.